Sugarcane green and sustainable harvest by demand management of the sugarcane harvester machine's spare parts - Fatemeh Afsharnia; Afshin Marzban; Mohammad Amin Asoodar; Abas Abdeshahi (Sustainable Futures, 2025)
Sugarcane (Saccharum officinarum L.), - as the raw material of sugar - is a highly perishable product that should be harvested green at the appropriate time to reduce environmental hazards. Sufficient stock of fast-moving spare parts could prepare the facilities for sugarcane green harvesting, minimize the loss of operating time, and reduce the adverse effect on the harvesting cost. Considering the importance of green sugar production, this study aimed to provide an approach based on real conditions of agro-industries to predict the required spare parts of a sugarcane harvester machine, namely CASE IH Austoft 7000. To forecast spare parts demand, we use a model that considers all factors affecting the number of used parts. In this paper, a novel approach for forecasting spare parts demand is developed based on parts' reliability, the operating environment, and their miscellaneous failure interaction. The failure interaction is evaluated by considering two, three, and n parts that are involved. This method is primarily motivated by the difficulty in forecasting the base cutter blade, chopper blade, and O-ring demand of the sugarcane harvester machine and it can be used for other industrial equipment to prevent production losses.